Effect of gamma irradiation on the nutritional quality of Agaricus bisporus strains cultivated in different composts - Andrade, Meire C. N.; Jesus, Joao P. F. [UNESP]; Vieira, Fabricio R. [UNESP]; Viana, Sthefany R. F. [UNESP]; Spoto, Marta H. F.; Minhoni, Marli T. A. [UNESP] (Acad Brasileira de Ciências, 2014)
The effect of irradiation doses (0, 125, 250 and 500 Gy) on the nutritional quality of A. bisporus mushrooms (strains ABI-07/06, ABI-05/03 and PB-1) cultivated in composts based on oat straw (Avena sativa) and brachiaria (Brachiaria sp.) was evaluated. The experimental design was 4 x 3 x 2 factorial scheme (irradiation doses x strains x composts), with 24 treatments, consisting of two repetitions each, totaling 48 experimental units (samples of mushrooms). The samples were irradiated in Cobalt-60 irradiator, model Gammacell 220 kGy, with dose rate of 0.740 kGy h(-1), according to the treatments proposed. Subsequently, the control (unirradiated) and the other treatments were maintained at 4 +/- 1 degrees C and 90% RH in a climatic chamber for carrying out the chemical analysis of the mushrooms on the 1st and 14th day of storage. It was found that all A. bisporus strains evaluated were food with excellent nutritional value, because they presented high protein and fiber contents and low ethereal extract content; the chemical characterization of the mushrooms was influenced by the compost type in which they were cultivated; gamma irradiation influenced the chemical composition of mushrooms.
Keywords: Agaricus bisporus; productivity; strains; compost; nutritional value